2023
DOI: 10.14689/enad.33.1592
|View full text |Cite
|
Sign up to set email alerts
|

Mistakes Made by Students While Posing Problems for Equations Containing Algebraic Fractional Expressions

Abstract: Conceptual and procedural knowledge has historically been one of the most discussed subjects in mathematics. In this study, errors in equations including algebraic fractional expressions were examined to determine where ninth-grade students in their comprehension of these expressions. The study employed a holistic multiple-case strategy, and the gathered data were evaluated using content analysis. The results indicate that students made the most mistakes with the definitions of quotient and fraction-whole. Cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Similarly, Marmur et al (2020) in their study with pre-service teachers found that the meaning they have the most is the part-whole meaning of the fraction, similar to this study. In the study carried out by Taştepe and Yanık (2021) it is seen that one of the meanings most used by 9th grade students when writing equations for algebraic fractional expressions is the part-whole meaning. Starting from pre-school, teaching focused on the part-whole meaning of fractions rather than other meanings may cause limited learning in students (Behr, Harel, Post, & Lesh, 1992;Haser & Ubuz, 2002;Okur & Cakmak, 2016;Toluk-Uçar, 2009).…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
“…Similarly, Marmur et al (2020) in their study with pre-service teachers found that the meaning they have the most is the part-whole meaning of the fraction, similar to this study. In the study carried out by Taştepe and Yanık (2021) it is seen that one of the meanings most used by 9th grade students when writing equations for algebraic fractional expressions is the part-whole meaning. Starting from pre-school, teaching focused on the part-whole meaning of fractions rather than other meanings may cause limited learning in students (Behr, Harel, Post, & Lesh, 1992;Haser & Ubuz, 2002;Okur & Cakmak, 2016;Toluk-Uçar, 2009).…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%